Antibacterial and anti-biofilm activities of probiotic Lactobacillus curvatus BSF206 and Pediococcus pentosaceus AC1-2 against Streptococcus mutans. (March 2022) - Luan, Chang; Jiang, Ning; Zhou, Xiaoling; Zhang, Chuang; Zhao, Yanping; Li, Zhengqiang; Li, Chen
Abstract: Streptococcus mutans ( S. mutans ) is the most important oral pathogenic bacterial cause of dental caries. Here we investigated the abilities of probiotic lactobacillus strains of Lactobacillus curvatus ( L. curvatus ) BSF206 and Pediococcus pentosaceus ( P. pentosaceus ) AC1-2 to control S. mutans . Both probiotic strains are acid and bile salt tolerant and are resistant to hydrogen peroxide and lysozyme to promote their survival within the oral environment. In addition, both strains are highly hydrophobic and are also capable of engaging in electrostatic interactions. These properties enhance abilities of both strains to adhere to gingival epithelial cells and HT-29 for improved colonization of oral tissues, while also enabling these probiotics auto-aggregate and to form aggregates with S. mutans that both may prevent S. mutans from colonizing oral tissues and facilitate the clearance of the cariogenic bacteria from the mouth during swallowing of food and saliva. Furthermore, results presented herein revealed that L. curvatus BSF206 and P. pentosaceus AC1-2 effectively inhibited S. mutans activities (biofilm formation, secretion of extracellular matrix components, synthesis of water-insoluble glucans) and led to downregulation of expression of key S. mutans genes involved in biofilm production ( gtfA, gtfB, ftf, brpA ). Taken together, these results indicate that L. curvatus BSF206 and P. pentosaceus AC1-2 can inhibit S. mutans biofilm formation as a new strategy for preventing dental caries. Highlights: The prebiotic properties of Lactobacillus curvatus BSF206 and Pediococcus pentosaceus AC1-2 were demonstrated. Lactobacillus curvatus BSF206 and Pediococcus pentosaceus AC1-2 could effectively inhibit the formation of S. mutans biofilm. The two strains reduced the synthesis of water-insoluble glucan, and inhibited some gene expression in S. mutans biofilm. The culture medium contained live lactobacillus was more effective in inhibiting biofilm than the bacteria-free supernatant.